New Qumran texts and studies : proceedings of the first Meeting of the International Organization for Qumran Studies, Paris, 1992 - Brooke, George J.; García Martínez, Florentino. (Studies on the Texts of the Desert of Judah, 1994)
New Qumran Texts and Studies contains 18 papers from the first meeting of the International Organization for Qumran Studies (Paris, 1992). Seven studies analyse parts of previously unedited texts: 4Q47 (A. Rofé, E.C. Ulrich), 4Q222 (J.C. VanderKam), 4Q265 (J.M. Baumgarten), 4Q286-290 (B. Nitzan), 4Q385ᴮ (D. Dimant), and the Psalm scrolls (P.W. Flint). Some of the other studies discuss various aspects of well known texts: 1QIsaᵃ (J. Cook), The Temple Scroll (L.H. Schiffman, D.D. Swanson), and the Hodayot (L. Vegas Montaner). Yet others cover a range of subjects: the publication process (E. Tov), the wilderness community (G.J. Brooke), the scrolls and the New Testament (J. Kampen, H.-W. Kuhn), computer aided scrolls research (A. Lange), dating (E.-M. Laperrousaz), and wisdom traditions (G.W. Nebe).